Gluconeogenesis and glycogenolysis required in metastatic breast cancer cells - Hicks, Emily; Layosa, Marjorie Anne; Andolino, Chaylen; Truffer, Caitlin; Song, Yazhen; Heden, Timothy D.; Donkin, Shawn S.; Teegarden, Dorothy (Frontiers in Oncology, 2024)
IntroductionMetabolic adaptability, including glucose metabolism, enables cells to survive multiple stressful environments. Glycogen may serve as a critical storage depot to provide a source of glucose during times of metabolic demand during the metastatic cascade; therefore, understanding glycogen metabolism is critical. Our goal was to determine mechanisms driving glycogen accumulation and its role in metastatic (MCF10CA1a) compared to nonmetastatic (MCF10A-ras) human breast cancer cells.Methodology13C6-glucose flux analysis in combination with inhibitors of the gluconeogenic pathway via phosphoenolpyruvate carboxykinase (PCK), the anaplerotic enzyme pyruvate carboxylase (PC), and the rate-limiting enzyme of the pentose phosphate pathway (PPP) glucose 6-phosphate dehydrogenase (G6PD). To determine the requirement of glycogenolysis for migration or survival in extracellular matrix (ECM) detached conditions, siRNA inhibition of glycogenolysis (liver glycogen phosphorylase, PYGL) or glycophagy (lysosomal enzyme α-acid glucosidase, GAA) enzymes was utilized.ResultsMetastatic MCF10CA1a cells had 20-fold greater glycogen levels compared to non-metastatic MCF10A-ras cells. Most glucose incorporated into glycogen of the MCF10CA1a cells was in the five 13C-containing glucose (M+5) instead of the expected M+6 glycogen-derived glucose moiety, which occurs through direct glucose conversion to glycogen. Furthermore, 13C6-glucose in glycogen was quickly reduced (~50%) following removal of 13C-glucose. Incorporation of 13C6-glucose into the M+5 glucose in the glycogen stores was reduced by inhibition of PCK, with additional contributions from flux through the PPP. Further, inhibition of PC reduced total glycogen content. However, PCK inhibition increased total unlabeled glucose accumulation into glycogen, suggesting an alternative pathway to glycogen accumulation. Inhibition of the rate-limiting steps in glycogenolysis (PYGL) or glycophagy (GAA) demonstrated that both enzymes are necessary to support MCF10CA1a, but not MCF10A-ras, cell migration. GAA inhibition, but not PYGL, reduced viability of MCF10CA1a cells, but not MCF10A-ras, in ECM detached conditions.ConclusionOur results indicate that increased glycogen accumulation is primarily mediated through the gluconeogenesis pathway and that glycogen utilization is required for both migration and ECM detached survival of metastatic MCF10CA1a cells. These results suggest that glycogen metabolism may play an important role in the progression of breast cancer metastasis.